Creative thinking and its relationship to academic achievement among students of the Institute of Sciences and Techniques of Physical and Sports Activities, University of M'sila - bachiri, benattia (sports creativity, 2025)
This study aims to determine the level of creative thinking and its relationship to academic achievement among students at the Institute of Sciences and Technologies of Physical and Sports Activities. The researcher hypothesized that a statistically significant relationship exists between creative thinking and academic achievement among these students. In light of the research objectives and the nature of the study, and to test the research hypotheses and assess their validity, the Sayed Khairallah Creative Thinking Test was administered to a sample of 60 second-year Master's students in the Physical Education Department. These students were divided into three levels based on their academic performance (good, average, and weak). The researcher reached the following conclusions: 1- The level of creative thinking among students in the Physical Education Department is high. 2- There is a direct relationship between creative thinking and academic achievement among students in the Physical Education Department.